Inovasi Olahan Pangan Bagi Masyarakat Desa Omuto Kec Biau Kabupaten Gorontalo Utara - Kasim, Faizal; Tuli, Munirah; Paramata, Arfiani Rizki (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
Omuto Village is one of the villages located in the Biau sub-district, Gorontalo Regency. To the north is Tapalu Village, Tenilo, Biau Village, to the east by Didingga Village, to the south by Potanga Village, the West to contigous with Molangga Village. The livelihoods of the people of Omuto Village are Farmers. Corn processing is still limited to processing for traditional foods such as milu siram. This type of traditional food has a low shelf life at a low selling price. Most of the corn commodities in Omuto Village are marketed in primary form (fresh corn) or shelled dry maize with a low selling value. This program of KKS Service activities aims to increase the added value of corn through the diversification of processed food. The target of this activity is so that the target group can acquire skills in processing various kinds of products made from corn, so that gradually they are motivated to develop businesses with a commercial-business mindset. This KKS Service activity will be carried out from September to October 2020. The technique used to socialize innovations in the field of food processing technology to the public is through communicative learning through training activities. Efforts to empower the community in Omuto Village are carried out by providing guidance and transfer of knowledge. technical skills and how to process corn commodities into processed products in the form of home industries